Respons growth and production of onion (Allium ascalonicum L.) on dose of thitonia’s liquid organic fertilizer (Tithonia diversifolia (Hemsl.) Gray) and interval of application time - riri azyyati (Jurnal Agroekoteknologi, 2016)
The objective of the research is to found dose of tithonia and interval of application time to increased growth and production of sallot. This research was conducted in Tanjung Anom, Medan Sunggal with altitude ± 25 meters above sea surface began from December to Februari 2016 used factorial randomized block design with two factors. The first factor was dose of thitonia’s liquid organic fertilizer (600, 900, dan 1200 ml/plant) and the second factor was interval of application time (4, 6, and 8 day to one). The result of this research showed that dose of thitonia’s liquid organic fertilize were significantly effect to number of leaves per clump parameter on 1 weeks after planting. Interval of application time were significantly effect to plant height on    4 weeks after planting, diameter tubers per sample, and sell dry weight per plot. Generally, the best treatment of the research was with dose of tithonia 1200 ml/plant and interval of 4 days for once application. The interaction of two factor not significantly affect on all parameters observed.Keywords : shallot, tithonia, dosage, interval of time